2008
DOI: 10.1016/j.bmc.2007.10.078
|View full text |Cite
|
Sign up to set email alerts
|

N-Phenyl-N′-(2-chloroethyl)ureas (CEUs) as potential antineoplastic agents. Part 3: Role of carbonyl groups in the covalent binding to the colchicine-binding site

Abstract: In the course of the development of N-phenyl-N'-(2-chloroethyl)ureas (CEUs) as potential antineoplastic agents, we investigated the effect of carbonylated substituting chains of the aromatic ring of CEU on their covalent binding to the colchicine-binding site (C-BS). In this study, we found that CEU, 5e, 5f, 8e, and 8f substituted by either a methyl ester or a methyl ketyl group at the omega-position exhibited a significant antiproliferative activity on HT-29, M21, and MCF-7 tumor cells. SDS-PAGE assays and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
3
18
0
1
Order By: Relevance
“…This adduct is easily detectable by Western blot as a second immunoreacting band of β-tubulin [16,21,[26][27][28][29]. As seen in Figure These results also show that that the TMP moiety is not essential for the affinity and the acylation of the C-BS.…”
Section: Sceus Acylate the Glutamic Acid Residue In Position 198 Of Tsupporting
confidence: 65%
“…This adduct is easily detectable by Western blot as a second immunoreacting band of β-tubulin [16,21,[26][27][28][29]. As seen in Figure These results also show that that the TMP moiety is not essential for the affinity and the acylation of the C-BS.…”
Section: Sceus Acylate the Glutamic Acid Residue In Position 198 Of Tsupporting
confidence: 65%
“…The acylation of Glu198 leads to microtubule depolymerization, hypoacetylation of Lys40 on α-tubulin, cytoskeleton disruption, and anoikis. 24,25 CEU analogues such as 1-(2-chloroethyl)-3-(4-iodophenyl)urea ( 5 ) 26−28 or 1-(2-chloroethyl)-3-(3-(5-hydroxypentyl)phenyl)urea ( 6 ) 2931 inhibit angiogenesis and tumor growth in three distinct animal models. (25) The biodistribution of CEU analogues to organs of the gastrointestinal tract suggests that they might be promising new drugs for the treatment of colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Previous SAR studies in our laboratory have demonstrated that both N-phenyl-N'-(2-chloroethyl)ureas (5a-5d) and their phenyl 2-aminoxazoline (6a, 6b) bioisosteric equivalents (Figure 1) could replace the 3,4,5-trimethoxyphenyl moiety (ring A) of CA-4 and bind to the C-BS with similar spatial conformations [34]- [42]. To further assess the potential of the N-phenyl-N'-(2-chloroethyl)urea moiety for the development of new VDAs derived from CA-4, we develop analogues with low-molecular weight derived from substituted phenyl 4-(2- oxoimidazolidin-1-yl)benzenesulfonates (PIB-SOs, 9-67) [43] and phenyl 4-(2-oxoimidazolidin-1-yl)benzenesulfonamides (PIB-SAs, A8-A48) [44], where the 2-chloroethylurea moiety is cyclized under basic conditions into the corresponding 2-imidazolidone ring.…”
Section: Introductionmentioning
confidence: 97%
“…PIB-SOs and PIB-SAs exhibit antiproliferative activities at the nanomolar level towards several tumor cell lines, bind to the C-BS, block cell cycle progression in G2-M phase, disrupt the cytoskeleton and show potent antineoplastic activity towards human fibrosarcoma (HT-1080) tumors grafted onto the chorioallantoic membrane of developing chicks, and low systemic toxicity towards the embryos [43] [44]. Based on SAR studies of N-phenyl-N'-(2-chloroethyl)ureas [34]- [42], we hypothesize that the phenyl 2-imidazolidinone moiety of PIB-SOs and PIB-SAs might also mimic the 3,4,5-trimethoxyphenylated ring A of CA-4 and could be used as a bioisosteric equivalent for the development of new VDAs derived from CA-4.…”
Section: Introductionmentioning
confidence: 99%